Belt-type electrical muscle stimulation preserves muscle fiber size but does not improve muscle function in a rat model of cancer cachexia - Karina Kouzaki; Mako Isemura; Yuki Tamura; Hiroyuki Uno; Shunta Tadano; Ryuji Akimoto; Katsu Hosoki; Koichi Nakazato (PLoS ONE, 2025)
Cancer cachexia causes severe muscle wasting, and current treatments remain limited. Belt-type electrical muscle stimulation (bEMS) has emerged as a passive rehabilitation tool capable of activating multiple lower limb muscles simultaneously. We investigated whether bEMS prevents muscle wasting and improves functional outcomes in rats with cancer cachexia. Cancer cachexia was induced in male Sprague-Dawley rats by intraperitoneal injection of AH130 Yoshida hepatoma cells. Acute and chronic effects of bEMS were tested. Muscle protein synthesis was evaluated using the SUnSET method, and muscle fiber cross-sectional area (CSA) and ankle torque were measured after chronic stimulation. bEMS increased puromycin-labeled protein levels on day 3 post-injection (~1.5–2.0 fold; p < 0.05). After 10 days, bEMS mitigated reductions in muscle CSA in the gastrocnemius and tibialis anterior compared to the cachexia group. However, muscle strength (ankle torque) was not significantly improved. bEMS preserved muscle fiber size in cancer cachexia but failed to restore muscle function. These findings suggest bEMS may serve as a supportive strategy against muscle atrophy in cachectic conditions.